Mdantsane : city, satellite or suburb? - Gordon, Timothy John (Rhodes University, Faculty of Science, Department of Geography, 1978)
The final step envisaged by present South African Government policy in respect of the black peoples of South Africa is the granting of political independence to the ten homelands which have been set aside for occupation by the various ethnic groups recognized by the. Government. This step represents the culmination of ideas that have developed regarding the separation of races since early in South Africa's history, and decisions that have been taken to implement them. Particularly since the first attempts to formulate black policy after Union in 1910, there have been protagonists of a segregationist policy, and the idea of some sort of self-government for the various races of South Africa has been evident 1n the country for many years. This idea was given greater stature in the policies of the national government after 1948, and in 1959 full political independence for the various black nations in South Africa became a political goal of the governing party. As this policy has progressed during the present decade, a number of new political areas have come into existence at various levels of the hierarchy of political areas. Intro. p. 1.
Keywords: Political geography; Black people -- Relocation -- South Africa -- Ciskei; Ciskei (South Africa) -- Politics and government